Evaluating the impact of advertising strategies on rural brand building: Insights from the personal care FMCG sector - Vinod Sharma; Chandan Maheshkar; Yogesh Mahajan; Sándor Remsei; Manohar Kapse (Innovative Marketing)
Type of the article: Research Article AbstractThis study examines how advertising strategies, namely, content, media, and design, influence brand-building efforts in rural markets, with a specific focus on the mediating role of content relevance. Anchored in the Elaboration Likelihood Model (ELM), the research recognizes that rural consumers often process advertising through the peripheral route, relying on visual, linguistic, and cultural cues rather than rational evaluation. Data were collected through a structured survey of 498 rural consumers across thirteen towns in Madhya Pradesh. Using covariance-based structural equation modelling, the study finds that advertising content (β = 0.353), media (β = 0.253), and design (β = 0.298) significantly affect brand perceptions. More importantly, content relevance emerges as a key mediator, with indirect effects ranging from β = 0.180 to 0.243 (p < 0.01), indicating that rural consumers are more likely to engage with advertising that aligns with their values, language, and lifestyle. Theoretically, the study extends the ELM framework to low-involvement consumer settings and highlights the nuanced role of cultural relevance in shaping brand engagement. Practically, the findings offer marketers a roadmap for creating locally adapted and emotionally resonant campaigns that move beyond urban-centric models. This research underscores the importance of designing inclusive advertising strategies that build lasting brand relationships with India’s diverse rural population.